Incidence and severity of rhizoctonia sp. in ten rice cultivars in greenhouse conditions. - Moreno, Nelson; Vivas, Leticia (Revista Universidad de Guayaquil, 2011)
In order to determine the incidence and severity caused by Rhizoctonia sp. Ten rice cultivars were evaluated: INIAP 415, INIAP 11, INIAP 12, INIAP 14, INIAP 15, INIAP 16, 1001, Fedearroz 50, GO 38151 and GO 38160, and inoculated 70 days after sowing in greenhouse conditions, they were observed every week since the first symptoms. The first symptoms of the disease were observed the third day after the inoculation. The broken pods symptom ranged between 5 and 7 days after inoculation in the different cultivars. The rupture of the culm symptoms were observed in INIAP cultivars. The highest incidence of Rhizoctonia sp. Showed up in INIAP 415 with 52.65%, Fedearroz 50 with 50.13% cultivars. The lowest incidence was observed in INIAP-12 with 28.70% and GO 38160 with 28,75% cultivars. INIAP 15 and INIAP 16 showed higher severity of the pathogen in their tillers with 30.92% and 30.01% of damage. The GO 38160 cultivar had less severity with 15.54%.